American soul [compact disc] - Watson, Aaron, 1977- (Big Label Records, 2021)
Aaron Watson's thirteenth studio album, and seventeenth album overall, since his debut in 2000. His last four studio albums have debuted in the top ten on the Billboard country album chart. To say that he is prolific as a writer and an artist is an understatement. Recorded just days before the COVID-19 shutdown, the 10 tracks take the listener on a journey of love, heartbreak, nostalgia, and pride.